HISTORY OF WORLD PEDAGOGICAL TEACHINGS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The history of world pedagogical teachings encompasses the evolution of educational practices and philosophies across various civilizations from ancient times to the contemporary era. This rich narrative reflects the diverse cultural, social, and political contexts in which education has developed, highlighting the ways societies have shaped their educational systems to meet their unique needs. Notable early educational frameworks emerged in ancient Egypt, China, India, Greece, and the Roman Empire, laying foundational principles that continue to influence modern education.[1][2][3]